The Out-Migration of Young Rural University Graduates : Macro Flows and Micro Motives - Rérat, Patrick (My University, 2014)
This paper addresses the migration of young graduates who do not go back to their rural home region after having attended university. Results from a case study in Switzerland show the need for research to combine a macro approach (analysis of the geography of graduates’ migration flows) with a micro approach (analysis of the motives reported by graduates), since self-reported motives are crucial to interpreting what is hidden behind the macro results.
The results from this case study indicate that graduates are attracted to urban settings not only for the labour market, but also for the living environment and social ties. The results also highlight the fact that migration decisions cannot be reduced to a single dimension. They are complex (in the sense that motives of several natures are involved in combination) and diverse (as differences are found within even a seemingly homogeneous population group). Although work is a central factor motivating the out-migration of graduates, the importance of social ties and residential amenities is also clear.
Keywords: Highly skilled migrants; Graduate migration; Internal migration; Out-migration; Rural region